Threshold-effect of ferritin levels with pathoglycemia in Chinese adults: a cross-sectional study based on China health and nutrition survey data - Chenyu Yang; Jintao Li; Chao Li; Jinyu Yang; Yanpei Gao; Guohua Li; Xintian Liu; Xiaoqin Luo (BMC Endocrine Disorders)
Abstract Background The present study aimed to explore the threshold-effect association of serum ferritin levels with type 2 diabetes mellitus (T2DM) and prediabetes mellitus in Chinese adults. Methods A total of 8365 people from CHNS a cross-sectional survey in 2009 were finally included. The biomarker data, including major cardiovascular biomarkers and important nutrition biomarkers were collected. The association of serum ferritin levels with T2DM and prediabetes mellitus were assessed by using restricted cubic spline function combined with multivariate logistic regression model. Results The mean age of the study subjects was 50.3 years, and 46.5% were men. The risk of T2DM and prediabetes mellitus increased when the ferritin level was greater than 140 ng/ml. The OR(OR = 0.59, 95% CI, 0.35–0.98)was lowest between 40 to < 60 ng/ml in men with prediabetes mellitus. The OR(OR = 0.61, 95% CI, 0.41–0.90)was lowest between 20 to < 40 ng/ml in women with prediabetes mellitus. Serum ferritin levels and OR value of women younger than 50 years old are lower than those of other participants. Conclusions There is a correlation between ferritin levels and pathoglycemia, with women under 50 years old having a lower risk for the same ferritin level, and maintaining low levels of ferritin can reduce the risk of developing diabetes mellitus.